MENTAL HEALTH THERAPY TRAINING IN YOUTH - Faida Annisa; Nina Rizka Rohmawati; Elok Triestuning (Institute for Research and Community Service, Health Polytechnic of Kerta Cendekia, Sidoarjo, 2021)
Community Service Activities in the form of Mental Health Therapy Training for Adolescents is one form of community service in the form of seminars aimed at conveying opinions or something new to participants, namely BK and teachers of Vocational High School in Sidoarjo with the hope that participants will get something new to be developed to become one thing that is broader about mental health therapy in adolescents. The activity was carried out on April 7, 2021 at the Health Polytechnic of Kerta Cendekia, Sidoarjo with the target being BK teachers at the Senior High School and Vocational High School levels in Sidoarjo. Before the activity was carried out, there was a process of preparing activities for 3 weeks before the activity was carried out, starting from the selection of extension materials to submission to related parties. As an evaluation, the activity was attended by BK teachers at the Senior High School and Vocational High School in Sidoarjo. Participants participated in these activities with enthusiasm and conducive, the activities can be carried out on time smoothly.